Molecular Identification of erm A and erm B, erm C genes in methicillin-resistant Staphylococcus aureus isolates from burns Patients and their association with multidrug resistance: erm A, erm B, erm C genes in MRSA - Mohammad, Sarmad Qassim; Awayid, Hussam Sami; Zarrouk-Mahjoub, Sinda; Jallil, Idriss Saleh (Cellular and Molecular Biology, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) is a significant hospital-acquired pathogen, particularly concerning in burn patients due to its multidrug resistance. This study aimed to assess the antibiotic sensitivity profile and identify the presence of erm genes (ermA, ermB, and ermC) associated with erythromycin resistance in MRSA isolates from burn patients. A total of 80 S. aureus isolates were collected from burn cases, with initial diagnoses performed using conventional culture and microscopic methods. MRSA isolates were confirmed using chromogenic agar media, and antibiotic susceptibility was determined via the disc diffusion method. Polymerase chain reaction (PCR) was employed to detect the erm genes responsible for macrolide resistance. Among 80 samples, 40 were identified as S. aureus, of which 18 were confirmed as MRSA. PCR analysis revealed the prevalence of ermA, ermB, and ermC genes at rates of 12%, 33%, and 11%, respectively. All MRSA isolates exhibited multidrug resistance to antibiotics, highlighting the challenge of treating infections in burn patients. This study underscores the critical need for molecular characterization of MRSA strains to inform effective therapeutic strategies and control their spread in burn wards.